(untitled) (Research, Society and Development, 2023)
The cultivation of soy (Glycine max) is one of the foundations of the Brazilian economy and currently due to national soil, it has been improving high production on the country’s agricultural sector, becoming the main product of agribusiness. The objective of the study was to monitor, through information gathering in the space-time scope, the production in tons and area destined to the planting of the culture in the state of Tocantins, between the years of 2008 and 2019. It was observed that the productive expansion soybean in the state of Tocantins is related to the increase in the area destined for the planting of legumes.